Model of investment-innovative development of economy of depression areas of the region - A. K. Ibraeva; D. M. Akisheva; A. Z. Zeynullina (Путеводитель предпринимателя)
The sources of financing investment and innovation activities are considered. Based on the analysis, a non&traditional source of investment in innovation is proposed – financial leasing. The objective need for the transition to the region’s economic growth and in the strategic plan for the phased transfer of economic systems to an innovative type of development based on a significant increase in investment activity in a market economy is shown, which is possible through a new scientific understanding of the economic nature of investments and the formation of an effective mechanism for their effective use in technological updating industrial sphere of depressed areas of the region.